Teknologi Recirculating Aquaculture System untuk Penanggulangan White Feces Disease pada Budidaya Udang Vaname Berbasis IoT - Rico Ade Irana Putra; Andrijani Sumarahinsih; Rifki Hari Romadhon (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Vannamei shrimp (Litopenaeus vannamei) is a high-value export commodity with strong demand in local and international markets. This shrimp species excels due to its adaptability, disease resistance, and delicious taste. However, white feces disease poses a serious threat, affecting the shrimp's digestive system, appetite, and growth. To prevent this, the recirculating aquaculture system (RAS) technology is a crucial innovation. This system maintains water quality and oxygen levels through continuous water and oxygen circulation, ensuring the health and productivity of vannamei shrimp.